Islamic Law Approach to Mitigate the Impact of Early Marriage: A Case Study in Sapeken district, Sumenep, Madura - Al Manar, Irwansyah; Thabrani, Abdul Mukhti; Zahroh, Fathimatuz (JUSTISI, 2025)
The study analyzed the impact of early marriage in Sapeken district, Sumenep, Madura, from the perspective of Islamic law, with a special emphasis on reproductive health, education, and the well-being of young women. This study investigates the social, cultural, and religious factors that drive the practice of early marriage as well as its negative effects. This research was conducted using a qualitative case study method. The results of the study showed that early marriage worsened physical and mental health, limited educational and employment opportunities, and increased women's economic dependence. Reproductive health education, premarital counselling, and economic empowerment programs are suggestions to address this problem. Following the principles of Maqasid Sharia which emphasizes the protection of individual life and welfare, religious leaders and community leaders have an important role in educating the public about the importance of physical and mental readiness before marriage. This method is expected to change the perspective of society and reduce the prevalence of early marriage. In addition, the study provides policy advice based on Islamic law that can improve the welfare of young women through the incorporation of social, educational, and health reforms in the island community